Alternativas de comercialización y exportación de aceites naturales, a partir del biocomercio en Colombia (2019)
Colombia is a country recognized worldwide for the diversity of its territory and natural resources, with a business sector that seeks to strengthen international markets, from which this work has been developed with the objective of identifying the marketing and export alternatives of natural oils that Colombia could have.